Patterns of Health Care Utilization in Vietnam : Analysis of 1997-98 Vietnam Living Standards Survey Data - Trivedi, Pravin K. (World Bank, Washington, DC, 2013)
The author provides an econometric analysis of health care utilization in Vietnam based on individual and household level data from the 1997-98 Vietnam Living Standards Survey. The author focuses on the major features of health care utilization patterns, including the determinants of largely self-prescribed use of pharmaceutical drugs, and the use of government hospitals, commune health centers, and private health facilities. The role of income and health insurance is emphasized. Econometric models are estimated for use probability and frequency of contact for all major categories of care, and for individual and household medical expenditure. Econometric results reveal differential responses to income changes at different levels of income. Commune health centers and self-medication are normal goods at lower income levels but inferior goods at higher income levels. The author discusses the policy implications of these results.